Evaluasi Pengembangan Materi Pembelajaran PAI - Erwina, Meifa Adinda; Arief, Asmaiwaty; Rehani (STAI Tebing Tinggi Deli, 2024)
The aim of the research is to evaluate the development of PAI learning materials found in this research. Islamic religious education (PAI) has a strategic role in forming the character of students who are faithful, devout and have noble character, as well as being relevant in facing the challenges of the modern era. PAI learning materials need to be developed dynamically with an interactive approach that integrates technology to meet student needs. The scientific approach in the 2013 Curriculum and the Merdeka Curriculum emphasizes the importance of cognitive, affective and psychomotor dimensions in learning. Evaluation based on Islamic education principles, both formative, summative and diagnostic, aims to ensure that learning materials support the holistic development of student character. This method uses the library research method by analyzing various written sources, such as books, journals and academic documents. Data was collected through relevant literature studies to understand the concepts, theories and practices of evaluating PAI materials. The research results show that a planned evaluation can be a diagnostic tool to identify weaknesses and strengths of material, thereby enabling better development. With evaluations that are oriented towards student needs and the challenges of the times, it is hoped that the development of PAI materials can produce a generation that excels academically and has a strong Islamic character.